2008
DOI: 10.1158/1541-7786.mcr-07-0243
|View full text |Cite
|
Sign up to set email alerts
|

Glioma Regression In vitro and In vivo by a Suicide Combined Treatment

Abstract: We present here a suicide therapy against malignant gliomas based on the transfer to tumor cells of a gene encoding a B-glucosidase, linamarase (lis), which in the presence of the innocuous substrate linamarin (lin) produces cyanide, blocking the mitochondrial respiratory chain. Dog glioma cells carrying the lis gene are thus sensitive to lin (IC 50 of 250 Mg/mL at 48 hours) and cell death is accompanied by mitochondrial fission and ATP depletion. The combination of lis/lin with an otherwise nontoxic level of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 40 publications
0
18
0
2
Order By: Relevance
“…Common therapeutic strategies include suicide gene therapy, oncolytic treatment, immunomodultion, gene replacement, proapoptotic treatment, and antiangiogenesis 175, 203. Successful delivery or efficacy of gene therapy approaches using viral vectors and plasmid DNA has been shown experimentally in canine brain tumor cells and brain using adenoviral,204, 205, 206, 207, 208, 209 retroviral201, 202, 210 herpes,211 and adeno‐associated viral212, 213, 214 delivery. Few viral therapies have progressed to phase III clinical trials, and none have been shown to have significant efficacy in high‐grade brain tumors in phase III trials to date 175…”
Section: Novel Therapiesmentioning
confidence: 99%
“…Common therapeutic strategies include suicide gene therapy, oncolytic treatment, immunomodultion, gene replacement, proapoptotic treatment, and antiangiogenesis 175, 203. Successful delivery or efficacy of gene therapy approaches using viral vectors and plasmid DNA has been shown experimentally in canine brain tumor cells and brain using adenoviral,204, 205, 206, 207, 208, 209 retroviral201, 202, 210 herpes,211 and adeno‐associated viral212, 213, 214 delivery. Few viral therapies have progressed to phase III clinical trials, and none have been shown to have significant efficacy in high‐grade brain tumors in phase III trials to date 175…”
Section: Novel Therapiesmentioning
confidence: 99%
“…Thus, tumor cells are sensitive to the blockage of autophagy (14,21) as well as to its stimulation (22)(23)(24). It has been previously demonstrated that autophagy is necessary for activated Ras-mediated transformation (7).…”
Section: Discussionmentioning
confidence: 99%
“…11 We have previously applied a suicide therapy against malignant dog glioma cells based on the transfer to tumor cells of a gene encoding a β-glucosidase, linamarase (lis), which, in the presence of the innocuous substrate linamarin (lin), inhibits the electron transport chain by the generation of cyanide that blocks the complex IV producing oxidative stress that increases the generation of autophagic vacuoles. 12 This block also disrupts the filamentous pattern of mitochondria, facilitating the engulfment of these damaged organelles by the generated autophagosomes. 12,13 The lis/lin system is combined with glucose oxidase (GO), which transforms glucose to gluconic acid and hydrogen peroxide, raising even more the oxidative stress and the generation of autophagic vesicles that in turn increases the efficiency of the lis/lin lethal effect.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…12 This block also disrupts the filamentous pattern of mitochondria, facilitating the engulfment of these damaged organelles by the generated autophagosomes. 12,13 The lis/lin system is combined with glucose oxidase (GO), which transforms glucose to gluconic acid and hydrogen peroxide, raising even more the oxidative stress and the generation of autophagic vesicles that in turn increases the efficiency of the lis/lin lethal effect.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
See 1 more Smart Citation